2014
DOI: 10.1371/journal.pone.0110328
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Distribution of Freshwater Amphipod Species in Switzerland (Crustacea: Amphipoda)

Abstract: Amphipods are key organisms in many freshwater systems and contribute substantially to the diversity and functioning of macroinvertebrate communities. Furthermore, they are commonly used as bioindicators and for ecotoxicological tests. For many areas, however, diversity and distribution of amphipods is inadequately known, which limits their use in ecological and ecotoxicological studies and handicaps conservation initiatives. We studied the diversity and distribution of amphipods in Switzerland (Central Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 53 publications
0
92
0
Order By: Relevance
“…In addition, we re-analysed these three species within a broader context of niphargids from Switzerland and showed that these three new species are endemic to Hölloch, ecologically diverse and phylogenetically not related. We conclude that this three-species amphipod assembly deserves special conservation attention according to all measures of biodiversity, as it parallels or exceeds a-and b-diversity patterns of amphipods or other aquatic macroinvertebrates in surface water systems in Switzerland (Altermatt et al, 2014;Altermatt, Seymour, & Martinez, 2013; but see Mamos, Wattier, Burzyński, & Grabowski, 2016).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, we re-analysed these three species within a broader context of niphargids from Switzerland and showed that these three new species are endemic to Hölloch, ecologically diverse and phylogenetically not related. We conclude that this three-species amphipod assembly deserves special conservation attention according to all measures of biodiversity, as it parallels or exceeds a-and b-diversity patterns of amphipods or other aquatic macroinvertebrates in surface water systems in Switzerland (Altermatt et al, 2014;Altermatt, Seymour, & Martinez, 2013; but see Mamos, Wattier, Burzyński, & Grabowski, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…Recent activities on amphipodology in Switzerland also mobilized cave societies (Altermatt et al, 2014). This resulted in several samples collected across Switzerland, including Hölloch cave system.…”
Section: Introductionmentioning
confidence: 99%
“…tridentinus Stoch, 1998 (sequenced using the same protocol as in Flot et al 2010; GenBank accession numbers KT878856 and KT878857) and pre-aligned in MAFFT using the FFT-NS-i mode to identify unsuitable sequences (originating from a different 28S region than our target region). After filtering out these sequences, the remaining dataset of 422 sequences from Lefébure et al (2006Lefébure et al ( , 2007, Fišer et al (2008), Trontelj et al (2009), Flot (2010, Flot et al (2010Flot et al ( , 2014, Hartke et al (2011), Trontelj et al (2012, Hekmatara et al (2013), Fišer et al (2013), McInerney et al (2014), Altermatt et al (2014), Ntakis et al (2015) and Esmaeili-Rineh et al (2015) were screened for perfect duplicates using FaBox (Villesen 2007), resulting in a dataset a 260 unique sequences, to which two outgroup sequences from the genera Synurella Wrzesniowski, 1877 and Gammarus Fabricius, 1775 were added as in Flot et al (2014). The sequences were aligned in MAFFT version 7 (Katoh & Standley 2013) using the E-INS-i option and analyzed in FastTree 2 (Price et al 2010) using the GTR model (Lanave et al 1984;Tavaré 1986) with 1000 bootstrap replicates (Felsenstein 1985).…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Crenobiont species are potentially endangered by impacts of climatic changes, especially if they have a restricted distribution area (Hering et al, 2009). Until now, studies referring to climatic changes in the context of freshwaters either concentrate on single species (Taubmann et al, 2011), a species group (Altermatt et al, 2014) or focus on general aquatic ecosystems (Daufresne et al, 2007;Khamis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%